FileNet: A Web-Based Research Repository System for IS-FIT UUM - Zahrah, Yahya (2006)
Information Retrieval system using web-based application has been implemented in many organization especially education institution at university level. The objectives of fleNet is to build effective research tools for researchers to access, explore and use the information, which may lead to improve research productivity and quality. fileNet has been developed for Information System department Universiti Utara Malaysia by using PHP, MySQL and Apache. The requirement model for fileNet was designed using the Unified Modeling Language (UML). This paper also discussed the web system methodology as proposed by Ginige as the methodology for system development. This paper concludes FileNet is the reliable and efficient for file storage and retrieval and also can enhance workgroup collaboration across functions and organization.